Soft magnetic member and its manufacturing method, and alloy plate material for soft magnetic member

JP7641488B2Active Publication Date: 2025-03-07DAIDO STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020117770
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-08
Publication Date
2025-03-07
Estimated Expiration
2040-07-08

AI Technical Summary

Benefits of technology

【0022】 上記した発明において、質量%で、C:0.020%以下、Mn:0.10%以下、P:0.010%以下、S:0.005%以下、Cu:0.05%以下、Ni:0.10%以下、Cr:0.10%以下、Mo:0.10%以下、Ti:0.010%以下、O:0.005%以下、N:0.005%以下、であることを特徴としてもよい。かかる特徴によれば、軟磁性部材として必要とされる磁気特性を満たす部材を高い製造安定性をもって得ることができるのである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641488000001
    Figure 0007641488000001
  • Figure 0007641488000002
    Figure 0007641488000002
  • Figure 0007641488000003
    Figure 0007641488000003
Patent Text Reader

Abstract

To provide an alloy for an Fe-Co-based soft magnetic member, a soft magnetic member, an intermediate thereof and a producing method thereof, in which the amount of Co added to Fe is adjusted and other elements are added, and which has excellent productivity without impairing cold workability and satisfies magnetic properties as a soft magnetic member.SOLUTION: The soft magnetic member has an alloy composition consisting of, by mass%, Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, Al: 0.10% to 2.00% (provided that the total amount of Si and Al is 1.00% to 3.00%), and Fe and unavoidable impurities as balance, and has an average crystal grain size of 40 μm or more and core loss under 1.5 T and 1 kHz of 150 W / kg or less. The soft magnetic member is obtained by processing strain introduced by cold working and recrystallization by heat treatment thereto.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Fe—Co-based alloy containing Si and Al for use in soft magnetic members, a soft magnetic member, an intermediate thereof, and methods for producing the same. [Background technology]

[0002] Magnetic steel sheets made of an alloy of Fe and Si are widely used as motor core materials because they can obtain magnetic properties such as high magnetic permeability (μ), low loss (Pcm), and high saturation magnetic flux density (Bs). On the other hand, in response to the recent demand for high output and miniaturization of motors, soft magnetic alloys in which Co is added to Fe have been developed to obtain higher saturation magnetic flux density. For example, Fe-49Co-2V material, commonly known as "Permendur," is known to have an excellent balance between saturation magnetic flux density (Bs) and magnetic permeability (μ). On the other hand, since Co is a very expensive element compared to Si and other elements, soft magnetic alloys with reduced Co content have also been proposed.

[0003] For example, Patent Document 1 discloses an Fe-Co based soft magnetic alloy containing Si and Al for forming magnetic parts such as transformer cores. When the Co content is less than 35%, Si and Al are added in accordance with the amount of Co. The alloy is subjected to cold rolling and annealing (heat treatment) multiple times to obtain a sheet or strip, and the upper limit of the amount of Co added is determined so as not to cause a rapid and sudden order-disorder transformation during this annealing treatment. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2018-529021 Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, Co is a very expensive element, and the above-mentioned electrical steel sheet containing a large amount of Co has a problem in terms of cost. Furthermore, the inclusion of a large amount of Co generates an embrittlement phase (ordered phase), and unless the processing and annealing conditions are properly controlled to ensure cold workability, it is impossible to form the steel into a desired product, which is also a problem in manufacturability.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an Fe-Co based alloy for soft magnetic members, which has excellent manufacturability without impairing cold workability by adjusting the amount of Co added to Fe and by adding other elements, and in particular, which has Si and Al added so as to suppress loss low, and which has soft magnetic properties as a soft magnetic member, a soft magnetic member, an intermediate thereof, and a manufacturing method thereof. [Means for solving the problem]

[0007] The Fe-Co based alloy for soft magnetic members according to the present invention is characterized by having an alloy composition, in mass%, of Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, Al: 0.10% to 2.00% (wherein the total amount of Si and Al is 1.00% to 3.00%), with the remainder being Fe and unavoidable impurities.

[0008] According to these characteristics, the magnetic properties required for a soft magnetic member are satisfied, and excellent cold workability is achieved, ensuring high manufacturability.

[0009] In the above invention, the alloy composition may contain, by mass%, C: 0.020% or less, Mn: 0.10% or less, P: 0.010% or less, S: 0.005% or less, Cu: 0.05% or less, Ni: 0.10% or less, Cr: 0.10% or less, Mo: 0.10% or less, Ti: 0.010% or less, O: 0.005% or less, and N: 0.005% or less. This feature ensures manufacturing stability, satisfies the magnetic properties required for a soft magnetic member, and ensures high manufacturability with excellent cold workability.

[0010] Furthermore, the present invention provides an alloy material for an Fe-Co based soft magnetic member, which has the above-mentioned alloy composition and has an average crystal grain size adjusted to 200 μm or less.

[0011] According to these characteristics, the magnetic properties required for a soft magnetic member are satisfied, and excellent cold workability is achieved, ensuring high manufacturability.

[0012] Furthermore, the preform material for an Fe-Co based soft magnetic member according to the present invention is a preform material for an Fe-Co based soft magnetic member that is subjected to a magnetic adjustment treatment by heating to provide a soft magnetic member, and is characterized in that it has the above-mentioned alloy composition and is provided with a cold-worked structure obtained by cold working.

[0013] According to this feature, by carrying out the magnetic adjustment treatment by heating, a recrystallized structure can be obtained, and the magnetic properties required for the soft magnetic member can be easily obtained.

[0014] In addition, the Fe-Co based soft magnetic member according to the present invention is characterized in that it has the above-mentioned alloy composition and is magnetically treated to have an average crystal grain size of 40 μm or more and a core loss of 150 W / kg or less at 1.5 T and 1 kHz.

[0015] According to these characteristics, the soft magnetic member has excellent manufacturability and high magnetic properties required for the soft magnetic member.

[0016] The above-mentioned invention may be characterized in that it has a recrystallized structure in which processing strain is released. With such a feature, the soft magnetic member has excellent manufacturability and high magnetic properties required for the soft magnetic member.

[0017] Furthermore, the present invention provides a method for producing a preform material for an Fe-Co based soft magnetic member, which is subjected to a magnetic adjustment treatment by heating to produce a soft magnetic member, and is characterized in that an alloy having an alloy composition, by mass%, of Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, Al: 0.10% to 2.00% (wherein the total amount of Si and Al is 1.00% to 3.00%), with the balance being Fe and unavoidable impurities, is prepared, with the average crystal grain size adjusted to 200 μm or less, and the alloy is cold worked to produce a cold worked structure.

[0018] According to this feature, by carrying out the magnetic adjustment process by heating, it is possible to obtain a preform material for easily obtaining the magnetic properties required for the soft magnetic member with high manufacturability.

[0019] In the above-mentioned invention, the composition may be characterized in that, by mass%, C: 0.020% or less, Mn: 0.10% or less, P: 0.010% or less, S: 0.005% or less, Cu: 0.05% or less, Ni: 0.10% or less, Cr: 0.10% or less, Mo: 0.10% or less, Ti: 0.010% or less, O: 0.005% or less, and N: 0.005% or less. According to such a feature, a preform material for easily obtaining a soft magnetic member can be obtained with high manufacturing stability.

[0020] Furthermore, a manufacturing method for an Fe-Co based soft magnetic member according to the present invention is a manufacturing method for an Fe-Co based soft magnetic member, which is characterized in that an alloy material having an alloy composition, by mass%, of Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, Al: 0.10% to 2.00% (wherein the total amount of Si and Al is 1.00% to 3.00%), with the remainder being Fe and unavoidable impurities, and having an average crystal grain size adjusted to 200 μm or less, is prepared, cold worked, heated, and subjected to a magnetic adjustment treatment to form a recrystallized structure having an average crystal grain size of 40 μm or more, and the core loss at 1.5 T and 1 kHz is set to 150 W / kg or less.

[0021] According to these features, it is possible to obtain, with high manufacturability, a component that satisfies the magnetic properties required for a soft magnetic component, by using the processing strain introduced by cold working and the recrystallization structure obtained by the heat treatment.

[0022] In the above-mentioned invention, the composition may be characterized in that, by mass%, C: 0.020% or less, Mn: 0.10% or less, P: 0.010% or less, S: 0.005% or less, Cu: 0.05% or less, Ni: 0.10% or less, Cr: 0.10% or less, Mo: 0.10% or less, Ti: 0.010% or less, O: 0.005% or less, and N: 0.005% or less. According to such a feature, a member satisfying the magnetic properties required as a soft magnetic member can be obtained with high manufacturing stability. [Brief description of the drawings]

[0023] [Figure 1] FIG. 4 is a flow diagram showing an example of a method for manufacturing a soft magnetic member according to the present invention. [Diagram 2] 1 is a list of the composition of alloys used in manufacturing tests. [Diagram 3] 1 is a table showing characteristics of soft magnetic members obtained in a manufacturing test. [Figure 4] 5A is a cross-sectional structure photograph of Example 6 after annealing, after cold working, and after magnetic adjustment treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] A soft magnetic member as one embodiment of the present invention, its intermediates, an alloy material for a soft magnetic member and a preform material for a soft magnetic member, and their manufacturing methods and an alloy for a soft magnetic member will be described with reference to FIG.

[0025] As shown in FIG. 1, in the method for producing a soft magnetic member, first, an alloy for a soft magnetic member having a predetermined component composition is melted and cast (S1).

[0026] Here, the alloy for soft magnetic members is an Fe-Co alloy, and its alloy composition contains, in mass%, Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, and Al: 0.10% to 2.00%, with the proviso that in this alloy composition, the total amount of Si and Al satisfies the condition of 1.00% to 3.00%.

[0027] In this way, by adjusting the amount of Co added to Fe and adding other elements to form an alloy composition, the required soft magnetic properties can be obtained at a high level in the final soft magnetic member without impairing cold workability.

[0028] In addition, in such an Fe-Co alloy, it is preferable to adjust the components so that the α / α+γ transformation point is 950° C. or higher. By increasing the transformation point, even if a magnetic adjustment treatment (magnetic annealing, heat treatment: S5) described later is performed, the remaining of the γ phase, which is an antiferromagnetic phase, is suppressed, and it becomes easy to obtain excellent magnetic properties as a soft magnetic member.

[0029] Furthermore, the alloy composition may contain, by mass%, C: 0.020% or less, Mn: 0.10% or less, P: 0.010% or less, S: 0.005% or less, Cu: 0.05% or less, Ni: 0.10% or less, Cr: 0.10% or less, Mo: 0.10% or less, Ti: 0.010% or less, O: 0.005% or less, and N: 0.005% or less. These are impurities that are desirably reduced as much as possible, and their inclusion is permitted within a range that does not affect the properties such as the magnetic characteristics of the soft magnetic member described above, but a manufacturing process that specifies them stabilizes the quality and increases manufacturing stability.

[0030] The cast alloy for soft magnetic members is then hot worked (S2). Here, the alloy is formed into the shape of an alloy material, such as a billet, by blooming, hot forging, and / or hot rolling, as described later. In the hot working, the heating temperature at least in the final strain application step is preferably lower than the α / α+γ transformation point, and is preferably 900°C or lower, for example. This suppresses the growth of crystal grains during the hot working, and the average crystal grain size of the alloy material for soft magnetic members obtained after annealing (S3), described later, can be 200 μm or less. By keeping the crystal grain size relatively small in this way, cracks in the cold working (S4), described later, can also be prevented. Note that the heating temperature in the steps other than the final strain application step in the hot working is also preferably lower than the α / α+γ transformation point in terms of maintaining the crystal grain size small, but may be higher in consideration of the load on the forging equipment.

[0031] Next, annealing is performed to remove processing strain (S3), and the average crystal grain size is adjusted to 200 μm or less to obtain an alloy material for soft magnetic members. Here, it is preferable to heat and hold at a temperature in the range of, for example, 700 to 900°C to prevent excessive grain growth. Depending on the processing strain in the hot working (S2), recrystallization may occur, which may also reduce the crystal grains and suppress grain growth. The alloy material obtained here may be, for example, a plate material with a thickness of 1.0 to 10.0 mm.

[0032] The alloy material prepared by annealing is cold worked (S4) to obtain a preform material for soft magnetic members with processing strain. Here, processing strain is imparted in advance to recrystallize and refine the crystal grains in the magnetic adjustment treatment (magnetic annealing, heat treatment: S5) described later. As the cold working, a known processing method such as cold rolling or cold drawing can be used. In addition, if the cold working cannot be performed in one pass, it can be processed in multiple passes. In this case, intermediate annealing may be performed between the cold workings to make it easier to perform the cold working. The intermediate annealing is performed at a temperature in the range of 600 to 900°C to remove processing strain that hinders the cold working and prevent excessive grain growth. This makes it possible to obtain a preform material for soft magnetic members having a cold worked structure that has been cold worked. The preform material for soft magnetic members can be, for example, a plate-like body with a thickness of 0.01 to 0.9 mm.

[0033] The obtained preform material for soft magnetic members is heated to perform a magnetic adjustment process (magnetic annealing: S5). This magnetic adjustment process is magnetic annealing for uniformly coarsening the crystal grains and reducing the core loss, and is preferably performed at a high temperature close to the α / α+γ transformation point. For example, the temperature is maintained within a range of 850 to 950°C in a non-oxidizing atmosphere such as a vacuum or ammonia decomposition gas. This uniformly coarsens the alloy structure, resulting in a structure with an average crystal grain size of 40 μm or more, and a soft magnetic member with excellent core loss can be obtained.

[0034] In this manner, the alloy for soft magnetic members is hot worked (S2) and then annealed (S3) to obtain an alloy material for soft magnetic members, which is then cold worked (S4) to obtain a preform material for soft magnetic members, and a soft magnetic member having a recrystallized structure due to the release of processing strain can be obtained after magnetic adjustment treatment (S5). In particular, by adjusting the Co content, the cold workability is not impaired, and the soft magnetic properties required for soft magnetic members can be obtained at a high level.

[0035] [Manufacturing test] Next, the test results of actually manufactured soft magnetic members will be described with reference to FIGS. 2 and 3. FIG.

[0036] As shown in FIG. 2, first, the alloys having the composition shown in each of Examples 1 to 7 and Comparative Examples 1 to 15 were melted in a vacuum induction furnace and cast into a 3.6 t steel ingot. The obtained steel ingot was divided, heated to 1100°C, hot forged, and then heated to 900°C (970°C only in Example 7) and hot rolled to produce a plate-shaped coil having a thickness of 3.5 mm. Furthermore, scale removal was performed, and annealing was performed by holding at a temperature of 750°C in a nitrogen atmosphere for 6 hours. Further, cold working was performed in the order of cold rolling, intermediate annealing, and cold rolling, to obtain a plate-shaped preform material for a soft magnetic member having a thickness of 0.2 mm. Thereafter, a magnetic adjustment treatment (magnetic annealing) was performed by holding at a temperature of 850°C or 950°C for 2 hours in an ammonia decomposition gas atmosphere to obtain a soft magnetic member.

[0037] As shown in Figure 3, the saturation magnetization (Js), core loss, and average grain size of the test pieces cut out from the final test material (soft magnetic member) were measured. The average grain size was also measured for test pieces cut out from a part of the test material after annealing (S3) (before cold working). The workability in cold working (S4) was also evaluated. The α / α+γ transformation point was calculated and recorded using the phase diagram calculation software Thermo-Calc 2020a and the alloy database FE6 based on the analyzed alloy composition (see the chemical composition in Figure 1). The target value of the transformation point was set to 950°C or higher.

[0038] The saturation magnetization (Js) was recorded as the magnetization value at a magnetic field strength Hm = 2000kA / m using a VSM (vibrating sample magnetometer) for a plate-shaped test piece with a thickness of 0.2 mm. The target value of saturation magnetization (Js) was set at 2.05T or more.

[0039] For core loss, a circular laminated core with an outer diameter of 28 mm, an inner diameter of 20 mm, and a thickness of 1 mm was fabricated by stacking five plate-shaped test pieces with a thickness of 0.2 mm, and was provided with a primary winding of 100 turns and a secondary winding of 100 turns. Using a known core loss measuring device, the loss Pcm of the laminated core when the primary winding was excited with a 1.5T, 1kHz sine wave AC magnetic field was measured and recorded based on the signal generated in the secondary winding. The target value for core loss under these conditions was set to 150W / kg or less.

[0040] The average grain size was measured for both the test material after annealing (S3) and the test material after the final magnetic adjustment treatment (S5) as described above. The average grain size was determined by observing the structure of the cut test piece in five fields of view at 25x or 50x magnification with an optical microscope and using the quadrature method.

[0041] After annealing (S3), if the average crystal grain size was 150 μm or less, it was recorded as good with a "◯", if it was between 150 μm and 200 μm, it was recorded as acceptable with a "△", and if it was over 200 μm, it was recorded as poor with an "X". In addition, after the magnetic adjustment treatment (S5) (after magnetic annealing), if the average crystal grain size was 40 μm or more, it was recorded as good with a "◯", and if it was less than 40 μm, it was recorded as poor with an "X".

[0042] The workability in cold working (S4) was evaluated based on the appearance of the test material after cold working, and was judged as follows: Those without cracks were marked as good with a "◯", those with some cracks but which could be made into a product shape were marked as acceptable with a "△", and those with cracks all over the surface and which could not be made into a product shape were marked as poor with a "X".

[0043] As shown in Fig. 3, in Examples 1 to 7, the α / α+γ transformation point was 950°C or higher, the saturation magnetization (Js) was 2.05T or higher, and the core loss was 150W / kg or lower, which met the target values. The average crystal grain size and workability were "good" in Examples 1 to 6, and the average crystal grain size and workability after annealing in Example 7 were "fair." The average crystal grain size after annealing in Example 7 was relatively large, which is thought to be due to the effect of increasing the hot rolling temperature.

[0044] For example, as shown in FIG. 4(a), in the cross-sectional structure photograph of Example 6 after annealing (S3), a structure with almost no directionality was observed. The average crystal grain size was 100 μm, which is 150 μm or less. Also, as shown in FIG. 4(b), in the cross-sectional structure photograph of Example 6 after cold working (S4), crystal grains extending in the left-right direction of the paper were observed, and it was found that the cold-worked structure was obtained. Also, as shown in FIG. 4(c), in the cross-sectional structure photograph of Example 6 after magnetic adjustment treatment (S5), a structure with linear crystal grain boundaries was observed, and it was found that the recrystallized structure had a structure with the processing strain released. The average crystal grain size of Example 6 after magnetic adjustment treatment (S5) was 50 μm, which is 40 μm or more.

[0045] As described above, according to Examples 1 to 7, it was possible to obtain magnetic properties required for a soft magnetic member, such as low core loss.

[0046] On the other hand, Comparative Examples 1 to 4 contain about 5 mass% Co, similarly to Example 1. Comparative Example 1 had a low transformation point and a small average crystal grain size after magnetic annealing (after magnetic adjustment treatment (S5)). As a result, the core loss was large, and the magnetic properties required for a soft magnetic member were not obtained. This is believed to be because neither Si nor Al was contained. Comparative Example 2 similarly had a low transformation point and a small average crystal grain size after magnetic annealing. As a result, the core loss was large, and the magnetic properties required for a soft magnetic member were not obtained. This is believed to be because Al was not contained. Comparative Example 3 had a transformation point of 950°C or higher, but the core loss was large, and the magnetic properties required for a soft magnetic member were not obtained. This is believed to be because Si was not contained. Comparative Example 4 had the magnetic properties required for a soft magnetic member, but the processability was poor. Although both Si and Al were contained, it is believed that the Si content was too high.

[0047] Comparative Examples 5 to 8 contain about 10 mass% Co, similar to Example 2. Comparative Examples 5 to 7 have different Co contents, but are similar to Comparative Examples 1 to 3, respectively. The same is thought to be true for the Si and Al contents. Comparative Example 8, like Comparative Example 4, obtained the magnetic properties required for a soft magnetic member, but the processability was poor. This is thought to be due to the Al content being too high.

[0048] Comparative Examples 9 to 14 contain about 18 mass% Co, similar to Examples 3 to 6. Comparative Examples 9 to 11 have different Co contents, but are similar to Comparative Examples 1 to 3, respectively. Comparative Example 12 has a large core loss. This is believed to be because the total amount of Si and Al was small. Comparative Example 13 has a small core loss, but the workability is poor. This is believed to be because the total amount of Si and Al is too high, and the content of Si alone is also high, while the content of Al alone is low. Comparative Example 14 has poor workability. This is believed to be because the total amount of Si and Al is too high, and the content of Si alone is also high.

[0049] Comparative Example 15 contained 27.2 mass% Co, which is more than that of the Examples. The transformation point was low, and the average crystal grain size after magnetic annealing was poor. As a result, the core loss was large and the workability was also poor. It is believed that the high Co content embrittled the material.

[0050] The composition range of the Fe-Co alloy capable of providing the soft magnetic members including the above-mentioned embodiments is determined as follows: First, the essential additive elements will be described.

[0051] Co is an essential element for ensuring the magnetic properties required for a soft magnetic member, particularly for obtaining a high saturation magnetic flux density Bs. On the other hand, excessive Co content generates an Fe-Co ordered phase, significantly embrittling the material, and also increases costs because Co is a very expensive raw material. Taking these factors into consideration, the Co content is within the range of 5.00% to 25.00% by mass.

[0052] Silicon increases the electrical resistance of the material, and also ensures low magnetocrystalline anisotropy constant and low magnetostriction constant, which are important in soft magnetic materials, and can significantly reduce iron loss Pcm when used in high frequency ranges. On the other hand, excessive silicon content leads to a decrease in saturation magnetic flux density Bs and embrittlement of the material. Taking these factors into consideration, the silicon content is within the range of 0.10% to 2.00%, preferably 1.00% to 2.00%, by mass.

[0053] Al increases the electrical resistance of the material, ensures a low magnetocrystalline anisotropy constant, which is important in soft magnetic materials, and can reduce iron loss Pcm when used in high frequency ranges. On the other hand, excessive Al content can lead to a decrease in saturation magnetic flux density Bs and embrittlement of the material. Taking these factors into consideration, the Al content is within the range of 0.10% to 2.00%, preferably 0.20% to 0.50%, by mass%.

[0054] In order to ensure the above-mentioned magnetic properties such as magnetic anisotropy, the total content of Si and Al has a lower limit, while an excessive total content of Si and Al leads to a decrease in saturation magnetic flux density Bs and embrittlement of the material. In consideration of these, the total content of Si and Al is in the range of 1.00% to 3.00%, preferably 1.40% to 3.00%, and more preferably 1.90% to 3.00%, by mass.

[0055] Next, elements that are impurities but are permitted to be contained in order to ensure production stability will be described.

[0056] Since C adversely affects the magnetic properties regardless of its state of existence, it is desirable to reduce it as much as possible. However, it is difficult to completely remove C that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable C content is 0.020% or less by mass.

[0057] Mn combines with S to form sulfides, which deteriorates the magnetic properties, so it is desirable to reduce the content as much as possible. However, it is difficult to completely remove Mn, which is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.10% or less by mass.

[0058] Since P has a detrimental effect on magnetic properties regardless of its state of existence, it is desirable to reduce it as much as possible. However, P is inevitably mixed in during manufacturing, and it is difficult to completely remove P. Therefore, taking into consideration the range in which it does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.010% or less by mass.

[0059] S is desirably reduced as much as possible because it combines with Mn to form residues that deteriorate the magnetic properties. However, it is difficult to completely remove S that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.005% or less by mass.

[0060] Cu has a detrimental effect on magnetic properties regardless of its state of existence, so it is desirable to reduce its content as much as possible. However, it is difficult to completely remove Cu that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.05% or less by mass.

[0061] Ni is an element having magnetism, but since it deteriorates the magnetic properties of the soft magnetic member of the above-mentioned embodiment, it is desirable to reduce the content of Ni as much as possible. However, it is difficult to remove Ni that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.10% or less by mass percent.

[0062] Since Cr has a detrimental effect on magnetic properties regardless of its state of existence, it is desirable to reduce it as much as possible. However, it is difficult to completely remove Cr that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.10% or less by mass.

[0063] Since Mo has a detrimental effect on magnetic properties regardless of its state of existence, it is desirable to reduce the content as much as possible. However, it is difficult to completely remove Mo that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.10% or less by mass.

[0064] It is desirable to reduce Ti as much as possible because it combines with C and N to form carbides and nitrides, which deteriorate the magnetic properties. However, it is difficult to completely remove Ti that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.010% or less by mass.

[0065] O combines with various elements to form oxide-based inclusions that are stable even at high temperatures, which deteriorates the magnetic properties, so it is desirable to reduce the content as much as possible. However, it is difficult to completely remove O that is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.005% or less by mass.

[0066] N combines with Al and Ti to form nitrides, which deteriorate the magnetic properties, so it is desirable to reduce the content as much as possible. However, it is difficult to completely remove N, which is inevitably mixed in during manufacturing. Therefore, taking into consideration the range that does not affect the magnetic properties of the soft magnetic member, the allowable content is 0.005% or less by mass.

[0067] Although typical embodiments of the present invention have been described above, the present invention is not necessarily limited to these, and a person skilled in the art will be able to find various alternative embodiments and modifications without departing from the spirit of the present invention or the scope of the appended claims.

Claims

1. In mass percent, Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, Al: 0.10% to 2.00%, (However, the total amount of Si and Al is 1.00% to 3.00%) The alloy plate material for an Fe-Co-based soft magnetic member is a plate-shaped alloy plate material having an alloy composition consisting of the remainder Fe and unavoidable impurities, and is characterized in having a recrystallized structure in which processing strain imparted by cold working has been released.

2. The Fe-Co based alloy plate for soft magnetic members according to claim 1, wherein the total content of Si and Al is 1.00% to 1.96%.

3. In the alloy composition, in mass %, C: 0.020% or less, Mn: 0.10% or less, P: 0.010% or less, S: 0.005% or less, Cu: 0.05% or less, Ni: 0.10% or less, Cr: 0.10% or less, Mo: 0.10% or less, Ti: 0.010% or less, O: 0.005% or less, N: 0.005% or less, 3. The Fe--Co based soft magnetic member alloy plate according to claim 1, further comprising:

4. The Fe-Co alloy plate for soft magnetic members according to claim 3, characterized in that the average crystal grain size is adjusted to 200 μm or less.

5. In mass %, Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, Al: 0.10% to 2.00%, (However, the total amount of Si and Al is 1.00% to 3.00%) The Fe-Co based soft magnetic member has an alloy composition consisting of the remainder Fe and unavoidable impurities, and is characterized in that it has been subjected to magnetic adjustment processing to have an average crystal grain size of 40 μm or more and a core loss of 150 W / kg or less at 1.5 T and 1 kHz.

6. The alloy composition, in mass percent, C: 0.020% or less, Mn: 0.10% or less, P: 0.010% or less, S: 0.005% or less, Cu: 0.05% or less, Ni: 0.10% or less, Cr: 0.10% or less, Mo: 0.10% or less, Ti: 0.010% or less, O: 0.005% or less, N: 0.005% or less, 6. The Fe--Co based soft magnetic member according to claim 5, characterized in that it comprises

7. 7. The Fe--Co based soft magnetic member according to claim 5, having a recrystallized structure in which processing strain has been released.

8. A method for producing an Fe—Co based soft magnetic member, comprising the steps of: In mass percent, Co: 5.00% to 25.00%, Si: 0.10% to 2.00%, Al: 0.10% to 2.00%, (However, the total amount of Si and Al is 1.00% to 3.00%) and preparing an alloy material having an alloy composition with the balance being Fe and unavoidable impurities and adjusted to an average crystal grain size of 200 μm or less, cold working the alloy material, heating the alloy material and applying a magnetic adjustment treatment to form a recrystallized structure having an average crystal grain size of 40 μm or more, and reducing the core loss at 1.5 T and 1 kHz to 150 W / kg or less.

9. In mass percent, C: 0.020% or less, Mn: 0.10% or less, P: 0.010% or less, S: 0.005% or less, Cu: 0.05% or less, Ni: 0.10% or less, Cr: 0.10% or less, Mo: 0.10% or less, Ti: 0.010% or less, O: 0.005% or less, N: 0.005% or less, 9. The method for producing an Fe—Co based soft magnetic member according to claim 8,

Citation Information

Patent Citations

  • Soft magnetic material

    JP1986253348A

  • Soft magnetic material

    JP1987093342A

  • Dust core

    JP2002075721A

  • Method for producing iron-cobalt-based alloy

    JP2007169760A

  • FeCo alloy, FeSi alloy or Fe sheet or strip and method for producing the same, magnetic transformer core produced from the sheet or strip, and transformer provided with the same

    JP2018529021A